The Interplay Between State Resilience Index Components and GDP Outcomes During Economic Crises - Saada Reuveni (Eximia, 2024)
The global economy is inherently dynamic, periodically facing crises that disrupt stability and growth. These crises—financial, environmental, or health-related—highlight the importance of resilience. This study explores the dynamic interplay between the State Resilience Index (SRI) components and Gross Domestic Product (GDP) outcomes during three significant economic crises: the Dot-Com Bubble (2000), the Global Financial Crisis (2007-2008), and the COVID-19 pandemic (2019-2021). By analyzing the performance of countries with varying SRI scores, we aim to understand how resilience factors contribute to economic stability and recovery. Through comprehensive statistical analyses of 100 countries, including detailed case studies of 25 nations, we find that nations with higher SRI scores not only manage downturns more effectively but also recover more swiftly, underscoring the critical role of resilience in long-term prosperity.